2003
DOI: 10.1161/01.cir.0000101926.43759.10
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Modulation of Cardiac Gap Junctions to Enhance Cardiac Conduction

Abstract: These data suggest that ZP123 significantly attenuates gap junction closure during acidosis. Preservation of intercellular coupling diminished CV slowing and heterogeneous repolarization, eliminating arrhythmogenic substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
112
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(130 citation statements)
references
References 32 publications
16
112
2
Order By: Relevance
“…Instead, we observed a more pronounced decrease of infarct size by RRNYRRNY compared with IP, indicating that preservation of gap junctional communication may be beneficial in mitoK ATPmediated cardioprotection. Given initial data that preservation of gap junctional communication during ischemia may also prevent cardiac arrhythmias (36) and that RRNYRRNY-related peptides may prevent uncoupling of cardiac gap junctions and action potential propagation block among cardiomyocytes (28), the combined targeting of mitochondrial and gap junctional Cx43 may prove an attractive clinical approach for protection against myocardial ischemia/reperfusion injury.…”
Section: See Retraction Published December 10 2012mentioning
confidence: 99%
“…Instead, we observed a more pronounced decrease of infarct size by RRNYRRNY compared with IP, indicating that preservation of gap junctional communication may be beneficial in mitoK ATPmediated cardioprotection. Given initial data that preservation of gap junctional communication during ischemia may also prevent cardiac arrhythmias (36) and that RRNYRRNY-related peptides may prevent uncoupling of cardiac gap junctions and action potential propagation block among cardiomyocytes (28), the combined targeting of mitochondrial and gap junctional Cx43 may prove an attractive clinical approach for protection against myocardial ischemia/reperfusion injury.…”
Section: See Retraction Published December 10 2012mentioning
confidence: 99%
“…Numerous studies highlight the importance of GJs in the genesis of cardiac arrhythmias, which has stimulated the search for antiarrhythmics targeting GJ channels (Eloff et al 2003). Several reports show that antiarrhythmic properties of the peptide AAP10 and its analogue ZP123, which is more resistant to proteolytic degradation in the digestive tract, are determined by decreased dispersion of activation and increased velocity of impulse conduction in the heart (Haugan et al 2005).…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%
“…In addition, ZP123 reduced the incidents of spontaneous ventricular arrhythmias of ischemic origin and size of infarct scars (Hennan et al 2006). It was suggested that these effects resulted from enhancement of intercellular communication, and it was shown that ZP123 does not affect the normal functioning myocardium but is protective during acidosis and metabolic stress (Eloff et al 2003, Haugan et al 2005). Thus, a new class of antiarrhythmic peptides that act on gap junctional communication may emerge.…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%
“…The acidosis-induced increase in APD dispersion was prevented by ZP123 administration in Langendorff-pefused guinea pig hearts. ZP123 diminished conduction velocity slowing and heterogeneous repolarization [148]. AAP10 enhanced gap junction conduction in guinea pig cardiomyocytes [149].…”
Section: The Possible Antiarrhythmic Effects Of Gap Junction Modulatorsmentioning
confidence: 96%
“…Ischaemia is associated with reduced sodium current (I Na ) that may cause conduction block [148] whereas the structural inhomogeneity and the increased gap junction resistance restore conduction [151,152]. On the other hand reduced intercellular coupling can limit the spread of mediators of cell death and this way it may reduce the size of infarction [153].…”
Section: The Possible Antiarrhythmic Effects Of Gap Junction Modulatorsmentioning
confidence: 99%